2022
DOI: 10.1371/journal.pone.0266662
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of mean population salt intakes using spot urine samples and associations with body mass index, hypertension, raised blood sugar and hypercholesterolemia: Findings from STEPS Survey 2019, Nepal

Abstract: Background High dietary salt intake is recognized as a risk factor for several non-communicable diseases (NCDs), in particular cardiovascular diseases (CVDs), including heart attack and stroke. Accurate measurement of population level salt intake is essential for setting targeted goals and plans for salt reduction strategies. We used a spot urine sample to estimate the mean population salt intake in Nepal and evaluated the association of salt intake with excess weight, hypertension, raised blood sugar and hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
(62 reference statements)
1
3
0
Order By: Relevance
“…Consistent to our results, several previous studies reported the presence of proportional biases of spot urine-based equations in the Bland–Altman plots indicating positive or negative correlation of individual difference with the average mean intake [28,31,33,39–41]. Salt intake estimated by the INTERSALT without potassium (8.51 ± 1.73 g/day) in the present study was closely consistent with the findings of recent WHO STEPwise approach to noncommunicable disease risk factor surveillance (STEPS survey) of Nepal using the same equation (9.1 ± 1.8 g/day) [42]. This indicates that the INTERSALT equations showed substantial underestimation of 24-h estimates in both studies, why application of these equations to estimate 24-h salt intake should be cautious in Nepal.…”
Section: Discussionsupporting
confidence: 89%
“…Consistent to our results, several previous studies reported the presence of proportional biases of spot urine-based equations in the Bland–Altman plots indicating positive or negative correlation of individual difference with the average mean intake [28,31,33,39–41]. Salt intake estimated by the INTERSALT without potassium (8.51 ± 1.73 g/day) in the present study was closely consistent with the findings of recent WHO STEPwise approach to noncommunicable disease risk factor surveillance (STEPS survey) of Nepal using the same equation (9.1 ± 1.8 g/day) [42]. This indicates that the INTERSALT equations showed substantial underestimation of 24-h estimates in both studies, why application of these equations to estimate 24-h salt intake should be cautious in Nepal.…”
Section: Discussionsupporting
confidence: 89%
“…Meanwhile, the dietary preferences brought about by gender make females prefer processed foods and snack foods compared to males [ 46 , 47 ], which can lead to higher sodium intake. While inconsistent with other studies, a relationship between BMI and sodium intake was not discovered, probably because of information bias in self-reported BMI by students as the primary reason [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 65%
“…Participants disposed of their first-morning urine at 5:00 a.m. on the first day, and all subsequent samples were collected. The method was accurate for gauging 24-hour urine completion in population-based biomarker investigations [9,19,20].…”
Section: Data Collectionmentioning
confidence: 99%